2013
DOI: 10.2147/nbhiv.s24888
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric effects of tenofovir in comparison with other antiretroviral drugs

Abstract: Abstract:Tenofovir is a widely used antiretroviral medication indicated to treat adults and children infected with HIV. Current guidelines for the management of HIV infection recommend tenofovir disoproxil fumarate (TDF) as a component of the preferred first-line combination antiretroviral therapy. The efficacy, tolerability, prolonged half-life allowing for once-daily administration, and availability as a component of several fixed-dose formulations make TDF an attractive choice for treatment-naive and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
1
0
0
Order By: Relevance
“…Tenofovir and lamivudine treated groups produced significant distortion of the cortical histomorphology. These results are in tandem with Ferrer and Rakhmanina (2013) who reported peripheral neuropathy in mice treated with tenofovir and the study of Peter et al (2017) who reported shrunken Purkinje cells and distorted granular layer in the cerebellum of rats treated with lamivudine. Several studies highlighting the detrimental effects that antiretroviral drugs have on neural structures are often through mechanisms involving oxidative stress.…”
Section: Discussionsupporting
confidence: 85%
“…Tenofovir and lamivudine treated groups produced significant distortion of the cortical histomorphology. These results are in tandem with Ferrer and Rakhmanina (2013) who reported peripheral neuropathy in mice treated with tenofovir and the study of Peter et al (2017) who reported shrunken Purkinje cells and distorted granular layer in the cerebellum of rats treated with lamivudine. Several studies highlighting the detrimental effects that antiretroviral drugs have on neural structures are often through mechanisms involving oxidative stress.…”
Section: Discussionsupporting
confidence: 85%